Todos podem aprender: uma intervenção com crianças do 3º ano do Ensino Fundamental com atrasos na aprendizagem da linguagem escrita - Souza, Noemi Tamar Américo de (2018)
This research has its origin in a question that is related to the great amount of children who reach the end of the 3rd year of elementary school, known as literacy cycle, without being able to read and write with proficiency. Studies have shown that performance in written language is directly related to the development of metalinguistic skills, more specifically phonological awareness, and that phonological-based pedagogical intervention programs have shown very positive results in reading and writing learning. So, the present study aimed to verify the impact of an explicit and systematic intervention composed of written language activities guided by phonic instruction with a group of children who, despite attending school for at least three years, had difficulties in their literacy process. Seven children enrolled in the 3rd year of primary education participated in this study of a public school in the city of São Paulo. The research was carried out in three phases: pre-test, intervention and post-test. evaluation of written language and phonological awareness were applied at the beginning and at the end of the intervention. The obtained results were transformed in percentage in order to verify the difference between the two moments of the research, before and after the intervention. The results showed that the intervention considerably improved the development of reading and writing abilities and phonological awareness in children, corroborating the results of previous researches